Pension data in European national accounts: ESA 2010 Table 29 - Filipo Gregorini (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2020)
The need for statistics on pensions is increasing as populations age and the choice of available pension schemes widens in many European Union (EU) Member States. As a response to this need, statistical authorities in the EU have been compiling a snapshot of future pensions (accrued entitlements) of households in pension schemes in Table 29 of the European System of National and Regional Accounts (ESA 2010). Information is compiled for both private and public schemes, including pay-as-you-go, defined benefit and social security pension schemes, for which figures are published in Eurostat's reference database and also nationally. Individual retirement schemes, not related to occupation, are excluded from the table. Pension figures crucially rely on a number of assumptions about the future, including the discount rate and life expectancies. Table 29 data transmission includes a sensitivity analysis to variations in the discount rate: this analysis provides information on how pension entitlements in defined benefit schemes would change in the case of a +/-1 percentage point change in the discount rate. The communication strategy for Table 29 data is considered to be crucial. Being calculated in terms of accrued-to-date liabilities, these statistics do not tell us anything about the sustainability of pension schemes themselves and conceptually should not be linked to government (Maastricht) debt. By contrast, enhanced pension reporting through Table 29 makes possible a comprehensive overview of households' pension entitlements, which comprise an important part of households' wealth and are therefore relevant for an analysis of households' consumption and saving behaviour.
Keywords: E21; G51; J11; M41; 330; national accounts; pensions; social insurance; household wealth; demographictrends; actuarial methods